Slang analysis of drag queen in the movie To Wong Foo, thanks for everything! Julie Newmar: sociolinguistic study - Yuniarti, Aslinda; Hartati, Elysa; Kameswara, Bagas Dwi (LP3M Universitas Islam Zainul Hasan Genggong, 2024)
This research was conducted to identify the slang employed by the drag queens in the film “To Wong Foo, Thanks For Everything! Julie Newmar” and how the slang is interpreted in the context. Qualitative descriptive research method was used to find out the meaning of the slang. The result showed a collection of slang identified in the film. It can be seen that in the context of a drag queen where a man with a manly appearance following a woman, the realization of the language used in the community follows the characteristic language of a woman. As the film often appears, the word 'Mama', 'Mamita' is used to refer to the same community to show a feeling of affection as a sexual identity and shows the language of feminism. Additionally, some slang that emerged with the addition of the suffix -a became 'gringa', -sies became 'looksies' and 'feelsies' also showed the characteristics of the gendered female language. In-depth study about slang in the context of drag queen is necessary to do. Further research can hopefully identify how this slang is formed when viewed from the perspective of the gender attribute.